Preservation of nasal septal cartilage in endoscopic transsphenoidal approach surgery - Taishi Nakamura; Yamato Oki; Kenta Fukui; Katsumi Sakata; Hiromitsu Hatakeyama; Tetsuya Yamamoto; Nobuhiko Oridate (Interdisciplinary Neurosurgery)
Background: The transseptal approach is widely used in a range of cases in endoscopic transsphenoidal neurosurgery. However, dissecting the mucosa from the septum can lead to perforation in some cases, and the resultant postoperative mucosal perforation can cause symptoms of discomfort, such as recurrent epistaxis, nasal crusting, headache, and nasal obstruction. In this study, we analyzed a technique for preserving the nasal septal cartilage to reduce nasal septal mucosal perforation in terms of the size and frequency of the perforations as well as the symptoms caused by them. We also evaluated the technical complexity of this technique and its potential to cause obstruction of vision and manipulation. Materials and methods: We enrolled a consecutive series of patients who underwent endoscopic transsphenoidal surgery using the nasal septal cartilage-preserving technique. Intraoperative and postoperative mucosal perforations of the nasal septum were confirmed. Results: Eighteen patients underwent surgery using this technique. Surgery was previously performed in only one patient with a pituitary neuroendocrine tumor. Among the other 17 patients who underwent primary surgery, seven showed intraoperative perforation of some size during detachment of the nasal septal mucosa from the nasal septum. Three cases, including a reoperation case, showed nasal septal perforation on outpatient examination a few months later, and no symptoms were associated with postoperative perforation in these three patients. Conclusion: Preserving the septal cartilage prevents perforation of the anterior component of the nasal septum and contributes to reducing the risk of postoperative perforation and its symptomatic occurrence without obstructing intraoperative manipulation.